Regulatory Governance in the ICT Industry - Inga KAWKA; Renata ŚLIWA (Communications of International Proceedings, 2021)
The paper puts forward the claim that for regulation to be adequate given the emerging challenges of the continuously developing disruptive ICT technology, it could increasingly benefit from a shift of reorientation towards a broader base of stakeholders that could serve as a supplement of sectoral regulatory decision-making. It is asserted that regulation is a meaningful element of contemporary rulemaking based on the common interest rationale (price and quality), individual security rationale (privacy) and business-core rationale (investment and innovation) as well as parallelly driven by mighty interest groups. There is a participatory approach that emerges towards more effective (interest-convergent and inclusive) development of the regulation of digital economy, especially as significant investment in the infrastructure and its deployment to achieve coverage objectives and to reinforce the robustness of regional networks are considered. The objective of the paper is to present the participation of stakeholders in regulatory processes as already developed ‘safeguards’ of regulator’s decisions in countries with high scores in fiber connections in total fixed broadband and penetration rate in fixed broadband. The participation of stakeholders is measured mainly by the spread of use of such instruments of participation in regulatory processes as public consultation and impact assessment. The widespread and formal use in ICT sector regulation of results of public consultations and impact assessments in selected countries may suggest their influence on regulatory risk-sensitive decisions on broadband networks.
Keywords: Regulation; Regulatory Governance; Stakeholder Participation in Regulatory Process; ICT Sector.